Traditional and Conservative Molar Endodontic Access Cavity Designs: A Classification and Overview - Vorster, Martin; van der Vyver, Peet J.; Markou, George (My University, 2022)
Minimally invasive endodontics' specific focus on dentine preservation is gaining popularity. Before deciding on the appropriate endodontic access cavity design, clinicians should investigate the advantages and disadvantages associated with different treatment modalities. The purpose of this article is to provide a summary of possible advantages and disadvantages of different endodontic access cavity designs with the focus on traditional, conservative and ultra-conservative endodontic access cavities, specifically in molar teeth. No conclusive evidence is found in the literature favouring one access cavity design above another and clinicians are advised to evaluate each case individually when deciding on the appropriate access cavity design for that specific case. Fracture resistance, proper shaping in order to facilitate irrigation and disinfection, as well as canal location and orifice detection are some of the contributing factors in selecting an appropriate access cavity design that will be highlighted in this article.